Improving outcome in severe trauma: trauma systems and initial management—intubation, ventilation and resuscitation. Issue 1044 (26th September 2012) - Harris, Tim; Davenport, Ross; Hurst, Tom; Jones, Jonathan
Abstract : Severe trauma is an increasing global problem mainly affecting fit and healthy younger adults. Improvements in the entire pathway of trauma care have led to improvements in outcome. Development of a regional trauma system based around a trauma centre is associated with a 15–50% reduction in mortality. Trauma teams led by senior doctors provide better care. Although intuitively advantageous, the involvement of doctors in the pre-hospital care of trauma patients currently lacks clear evidence of benefit. Poor airway management is consistently identified as a cause of avoidable morbidity and mortality. Rapid sequence induction/intubation is frequently indicated but the ideal drugs have yet to be identified. The benefits of cricoid pressure are not clear cut. Dogmas in the management of pneumothoraces have been challenged: chest x-ray has a role in the diagnosis of tension pneumothoraces, needle aspiration may be ineffective, and small pneumothoraces can be managed conservatively. Identification of significant haemorrhage can be difficult and specific early resuscitation goals are not easily definable. A hypotensive approach may limit further bleeding but could worsen significant brain injury. The ideal initial resuscitation fluid remains controversial. In appropriately selected patients early aggressive blood product resuscitation is beneficial. Hypothermia can exacerbate bleeding and the benefit in traumatic brain injury is not adequately studied for firm recommendations.